SIMPATISME PUBLIK SEBAGAI MOBILISASI POLITIK DI RUANG DIGITAL (Studi Para Figur Kegamaan Di Media Sosial) - Rosana, Ellya; Salim, Luthfi; Mahfudin Setiawan, Agus; Massay, Emmanuel Michael (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
The digital space has changed the political structure in Indonesia, which is influenced by religious figures. Because they have social capital from the capability of public trust in their knowledge and insights that are easy to understand, so they become role models to attract public sympathy in politics. Public sympathizers have unwittingly provided voluntary support to political groups on social media via the hashtag (#) to convey political issues and government policies. This study aims to discuss religious figures becoming public sympathizers and public sympathy in mobilizing politics in the digital space.qualitative research with phenomenological and multiple case approaches. Research data is obtained directly from digital platforms. First research results,shows that religious figures become public sympathizers, influenced by the content of lectures or articles containing social, political and religious insights, advice and inspiration through popular digital platforms, namely YouTube and Tiktok. Second, public sympathy in mobilizing politics is influenced by religious figures who utilize their social capital, such as 1) Social networks as a way to organize, collect, spread messages and gather public support in political activities. 2) Authority and Influence as political mobilization because religious figures are respected, have charisma, have good morals, broad social and religious insight, so they can motivate people to take political action. 3) Communication skills as material for conveying messages of goodness, insight and inspiration for goodness.